Effect of an anionic surfactant (SDS) on the photoluminescence of graphene oxide (GO) in acidic and alkaline medium. Issue 1 (2nd January 2018) - Saha, Prosenjit; Pyne, Dinesh Kumar; Ghosh, Srijon; Banerjee, Soumadip; Das, Sourav; Ghosh, Soumen; Dutta, Partha; Halder, Arnab
Abstract : An anionic surfactant (SDS) modulates the photoluminescence of graphene oxide (GO) in both acidic and alkaline medium. Abstract : An anionic surfactant (SDS) modulates the photoluminescence of graphene oxide (GO) in both acidic and alkaline medium. In the acidic medium (pH ≈ 2), formation of hemi spherical surface micelles on the GO sheets creates a non-polar environment around the flourophoric moiety of GO and hinders the solvent relaxation. This leads to a significant 36 nm blue shift of the photoluminescence band, whereas in alkaline medium (pH ≈ 10), SDS interacts with GO sheets in a different way due to the presence of negatively charged carboxylate ions at the GO edges. The repulsion between the negatively charged GO sheets and the intercalation of SDS within the basal planes of GO may weaken π–π stacking interaction which produces largely separate layers of GO. The largely separated GO sheets due to very weak stacking interactions among successive layers may behave almost like isolated functionalized GO, resulting in an enhancement of the photoluminescence intensity at 303 nm.